2010
DOI: 10.1590/s1676-06032010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Ecologic salience and agreement on the identification of tree species from Brazilian Atlantic Forest

Abstract: agreement on the identification of tree species from Brazilian Atlantic Forest. Biota Neotrop. 10(1): http:// www.biotaneotropica.org.br/v10n1/en/abstract?article+bn01310012010Abstract: This study aims to investigate the consensus among informants in the naming of tree species from a high diversity environment, the Brazilian Atlantic Forest (Sete Barras, SP), through a methodological procedure based on standardized stimuli. Seven selected local experts on tree species used for timber and handicrafts were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Thus, landscape units can be defined as ecotopes and can be classified with respect to their history, specific use and management, biotic and abiotic characteristics, cultural meaning and the possession of an indigenous name or names that originates from the migrant peoples’ language [15,16]. Ethnoecological studies focused on plant species generally assess local ecological knowledge, species use, and social relations with the species and can be very useful in explaining the characteristics of landscape units or ecotopes [15-19]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, landscape units can be defined as ecotopes and can be classified with respect to their history, specific use and management, biotic and abiotic characteristics, cultural meaning and the possession of an indigenous name or names that originates from the migrant peoples’ language [15,16]. Ethnoecological studies focused on plant species generally assess local ecological knowledge, species use, and social relations with the species and can be very useful in explaining the characteristics of landscape units or ecotopes [15-19]. …”
Section: Introductionmentioning
confidence: 99%
“…There was unanimity for only four species. An ethnobotanical study by Hanazaki, Mazzeo, Duarte, Souza, and Rodrigues () of folk knowledge of forest trees in Brazil also found a relatively low level of agreement among its seven informants. They reported that close to half of all the species studied were identified by only one or two informants and only 2% were identified by all seven informants.…”
Section: Discussionmentioning
confidence: 98%
“…They comment that,
… knowledge about tree species … is not shared among all informants, even though these seven informants were indicated as the experts about tree knowledge in this region. The local knowledge about tree species is not homogeneous, indicating a high variation in the local knowledge about a diversified assemblage of tree species (Hanazaki et al, :83).
…”
Section: Discussionmentioning
confidence: 99%
“…The inventory interview included more citations of species recorded in the vegetation because ecological characteristics are of great importance in the recognition of plant species by parataxonomists [8,14]. The only limitation would be the difficulty of relocating elderly informants or those with limited mobility to the field.…”
Section: Discussionmentioning
confidence: 99%